PENERAPAN SANKSI PIDANA TA‘ZÎR BAGI PELAKU TINDAK PIDANA KORUPSI DI INDONESIA - Endang Jumali (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2014)
Corruption is a criminal act which is getting the attention of many people. So, it need to get attention from the perspective of Islamic Criminal Law, both conceptually and operationally. Therefore, this paper is not only describe the historical development of concepts and theories of Islamic criminal law relating to the criminal law of corruption, but also specifically explained about nazhariyyah al-ta‘zîr criticism in legal theory of Ta‘zîr to the Law 20 of 2001 on the Eradication of Corruption. The main purpose of this article is to provide an overview of the theoretical possibility of ta‘zîr sanctions for perpetrators of corruption in Indonesia through nazhariyyah al-ta‘zîr and its relevance to the Law Number 20 Year 2001 on Eradication of Corruption.